PENERAPAN MEDIA PEMBELAJARAN LIVEWIRE TERHADAP HASIL BELAJAR PESERTA DIDIK SMAN 6 TENTANG LISTRIK DINAMIS - Atisah, Yekti; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the implementation of media physics learning using livewire against the learning outcomes of students of class X SMA 6 Pontianak about the power dynamic. A form of research in the form of a quasi-experimental design with design nonequivalent control group design. Determination of sample using a purposive sampling technique so that the obtained class X IPA 3 as the experimental class numbered 33 people and class X IPA 4 as the control class numbered 33 people. The research results obtained, namely: (1) Acquisition of the average score of pre-test and post-test in the experimental class 40,00 and 75,76 whereas in the control class 39,09 and 53,64; (2) there are differences in learning outcomes between learners before and after the used learning media livewire, based on the data analysis test U-Mann Whitney obtained value of sig (2-tailed) of 0,000 < 0,05; (3) the value of effect size 1.6 is included in the high category; (4) student responses 80.57% with the score interpretation criteria classified as good. The results of this study are expected to be an alternative in an effort to improve the learning outcomes of students on the material power dynamic.Â Keywords: Learning media, livewire, the learning outcomes, the power dynamic.